Effectiveness of Women's Self-care Instructions concerning Wound, Perineal & Urinary System Care post cesarean section in Baghdad teaching hospital - Kadhim, amel; ali, Rabea (Iraqi National Journal of Nursing Specialties, 2018)
Aim: to determine the effectiveness of women's self-care instructions on their post cesarean section care in Baghdadteaching hospital.Methodology: The present study used quasi-experimental study design in maternity words in Baghdad teachinghospital. The sample was collected and follow up for the period (15) January 2014 until 15 May 2014 Nonprobability(purposive sample) of (100) women post cesarean section divided in to two groups (50) women postcesarean section considered as a study group, and another (50) women post cesarean section considered as thecontrol one, A questionnaire designed as a tool to collect data fit the purpose of the study a questionnaire includedemographic variables, Reproductive variables, instructions self-care post cesarean Wound care, a pilot study wascarried out to test the reliability, As for reliability of questionnaire has been displayed by a group of experts invarious medical specialties and nursing.Result: The study presents significant differences in implementation of instructional program for self-carepost cesarean between study and control groups on wound, there is significant differences in washing handbefore & after any procedure, Don't put ointment or cream on the wound, don't raise the dressing to see operationimmediately unless done by medical staff (P=0.000). Also significant differences are found in perineal care &urinary system post cesarean in washing hand before & after using bathroom, wash perineum area water warmwater contains a antiseptics from front of the pubic bone to the anus, place sanitary pads from front to back toprotect the inner surface from contamination, do not hold on the urine when feel the desire to urinate,practice kegel exercises 2-3 times per day, Do not have sexual intercourse during the first 6 weeks, preferred touse the western bathroom (P= 0.000).Recommendations: The study recommended the possibility of providing an educational overlap of self-careafter a cesarean delivery for all pregnant women attending antenatal care centers, primary health, constructionand application of the overlap of the mothers of the educational process to be holding them in the hospital toincrease their knowledge of self-care after a cesarean section